Strengthening Digital Literacy in Determining the Attitude of Milenials in Online Shopping in SMA Yaspenmas - Ratna Sari; Ahmad Fadli; Amin Hou; Ester Hervina Sihombing; Ratih Amelia (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The use of digital media, which is currently a necessity for almost all human activities, creates many positive things that are useful for humans but also creates various negative consequences such as fraud, disturbed privacy and incorrect information (hoaxes) which are considered a serious problem in the digital era. . This indicates the low digital literacy of the community. The problems that arise are the large number of Internet users and the high frequency of people accessing information content and social media, especially among students and the millennial generation not accompanied by sufficient skills and knowledge which can result in losses for users, the rise of emerging online shopping applications is currently a phenomenon that changes the pattern of transactions from those that used to be offline now can be done by shopping, but this change in pattern has consequences for the seller and buyers in the form of losses and fraud that might occur if users of this application do not properly understand the ins and outs of it. This community service uses training and counseling methods as well as practices on how to use digital media as a way to shop online for students (students) so they can understand and be wise in utilizing digital media through increasing understanding of digital literacy with digital skills, digital culture, digital ethics, and digital safety